need for specific first aid and emergency knowledge whilst trekking in remote areas - results of the ADEMED (Aachen DEntal and MEDical) Expedition to the Annapurna region, Nepal - C. Scharfenberg; K. Lechner; S. v.d. Giet; M. Hettlich; V. Schöffl; A. Morrison; Thomas Küpper (University of Applied Sciences in Tarnow, Poland, 2021)
Introduction: Fellow trekkers are often the first responders to their comrades in remote settings. Not everyone undertakes First Aid (FA) training when travelling to remote settings away from comprehensive healthcare, whether travelling independently or in a group. The syllabus of standard urbanised FA courses does not fully cover the needs of such trekkers (ie altitude illnesses). We evaluated the FA and emergency knowledge of trekkers en route in the remote Nepalese Himalayas. Material and methods: A questionnaire about FA, trekking emergencies and water hygiene knowledge was completed by a cohort of 453 trekkers passing through Manang (3,519 m), Nepal, who volunteered their participation. A previously validated questionnaire consisted of 20 multiple choice questions (each using a five-point Likert scale) was used, followed by a subjective self-assessment of 17 key topics using a 5-point rating scale from very good to unsatisfactory knowledge. Demographic data including FA and climbing experience was also collected. Results: The participants generally showed a poor knowledge in FA and trekking emergencies, even though 20.8% had some occupational medical training. In total 59.5% of possible answers were answered correctly. On average each participant managed to answer only one out of 20 questions (5.4%) completely correct. The most unsatisfactory results concerned the following topics, each with only 2.4% correct answers: hypothermia/resuscitation, rescue strategies and rip fractures. The best results were for HACE 33.8%, cranio-cerebral injury 33.6%, angina pectoris/heart attack 31.8% and hypovolemic shock 28.7%. The majority of participants had very limited experience of climbing mountains, rock climbing or ice climbing. Conclusions: This study provides essential data identifying deficiencies in standard FA courses that are targeted for urban settings, and not for trekkers in a remote setting far away from comprehensive health care and rescue. There is a need to develop readily accessible FA curriculums specific to trekkers that would provide education on preventative care prior to, during, and after treks, and to improve their knowledge of medical care of trekking injuries and emergencies.